The Effect of Coumarin Derivatives(compounds) on the Vibrio cholerae Isolates from Different Clinical Iraqi Sources - Fatima .R.Abdul; Nehad .A.Taher; Ashraf S.Hassan; Enaam H. Batah (College of Pharmacy University of Baghdad, 2017)
From a large number of bacterial samples collected from different hospital in Iraq in central  health laboratory ,only ten isolates were identified primary as Vibrio. A number of  morphology and biochemical test were carried out to complete this identification that showed all bacterial isolates were related to Vibrio cholerae .In this study  all Vibrio isolates were investigated for Bio typing and the result showed that all (10) isolate were related to (Eltor biotypes) .Also, the susceptibility test towards eight antibiotics were carried  out . Results shows that  ciprofloxacin , Norfloxacin, Erythromycin, Ampicillin,  ceftriaxone  and Amikacin were the most effective antibiotics and their resistance percentage were 20%,20%,20, 20,30% and 30% respectively ,While  Chloramphenicol  and Co- trimoxazole were less effective and their resistance percentage were 90% both of them. Three (3,5,6) isolates V. cholerae were selected depending on results of antibiotics sensitivity tests as showed multiple -antibiotics resistance(100%).                                                                                 Then tested to study the effect of coumarin derivatives compounds (1, 2, 3 ) which showed inhibitory effect on V. cholera (3,5,6) isolates and the compound ( 3 ) showed the  highest antibacterial activity of (12,15,14 mm) of inhibition zone diameter against V. cholera (3,5,6) isolates respectively.  Also, these Iraqi isolates (3,5,6) used to test the effect of acridine orange  (0.1%) as acuring agent , the results showed that all (3)  isolates V. cholerae were  sensitive to (ciprofloxacin, ceftrixone and Norfloxacin), While the rest were resistance to remained five antibiotics. The results of Agarose -gel electrophoresis of both  normal V. cholerae (3,5,6) and cured isolates showed the presence of chromosomal and plasmid DNA bands in the normal case ,While only chromosomal DNA bands occur with V. cholerae (isolate 8) treated  with an acridine orange at concentration of (10-2 to 10-4).